Ionic Liquids: A Tool for Halal Food Industry - Elgharbawy, Amal A.M.; Azmi, Nor Azrini Nadiah; Mohd. Salleh, Hamzah (2019)
Currently, replacing volatile organic solvents with ionic liquids (ILs) in industrial applications is a matter of concern. ILs became solvents of choice due to their properties such as low melting points (<100 °C) and negligible vapor pressure. Despite being expansively investigated, ILs have not yet been intensively reviewed as eco-friendly solvents for the halal industry, which is the aim of this work. ILs have been used as surfactants, extractants for the purification of biomolecules, stabilizers for enzymes and in biosensors applications. Regardless of the lack of data on the toxicity of food products with ILs residues, low doses of ILs in in vitro tests did not lead to cell damage. Moreover, several ILs have stabilizing effects on biomolecules such as enzymes and proteins. Thus, new applications of ILs in the halal industry are possible within the concept of halalan tayyiban.